Is photodynamic diagnosis ready for introduction in urological clinical practice?. Issue 6 (June 2013) - Cordeiro, Ernesto R; Anastasiadis, Anastasios; Bus, Mieke TJ; Alivizatos, Gerasimos; de la Rosette, Jean JMCH; de Reijke, Theo M
The aim of this review is to provide an up-to-date review of the available literature on photodynamic diagnosis (PDD) for nonmuscle-invasive bladder cancer, to present the technique in a comprehensive approach and, finally, to discuss the relevance of PDD in clinical practice in terms of indications, outcomes and its development trend. A literature search was conducted up to July 2012, using MEDLINE and EMBASE via Ovid databases to identify published studies on PDD for nonmuscle-invasive bladder cancer. Only English-language and human-based full manuscripts that reported on case series and studies with >40 participants, concerning clinical evidence of the technique, its efficacy and safety data were included. Evidence showed that PDD significantly improves detection of bladder cancer compared with standard white-light cystoscopy, having proven to be more effective for the diagnosis of carcinoma in situ . This condition seems to facilitate more complete resections, resulting in a lower residual tumor rate, which, in turn consecutively leads to higher recurrence-free survival rates. The literature search demonstrated that for mid- and long-term follow-up, PDD showed acceptable outcomes in terms of tumor detection, as well as lower residual tumor and lower recurrence rates compared with white-light cystoscopy. It has proven to be safe and well tolerated; the major limitations of PDD are its low specificity and elevated costs.